The landscape of precision cancer medicine clinical trials in the United States. Issue 5 (May 2015) - Roper, Nitin; Stensland, Kristian D.; Hendricks, Ryan; Galsky, Matthew D.
Highlights We identified 684 precision cancer medicine trials from ClinicalTrials.gov. 38 unique genomic alterations were identified for enrollment. These trials were more likely to involve breast, colorectal and skin cancers. The proportion of these trials increased from 3% in 2006 to 16% in 2013.